Tantangan Dakwah: Tinjauan Faktual Kekosongan Dai Pada Bulan Suci Ramadhan Di Masjid Darussalam Kampung Pisang Kota Sorong - Sitti Mutia Faradillah (JASNA : Journal For Aswaja Studies, 2022)
AbstractThe  purpose  of  the  study to  examine  the factors causing  the constrained activities  of  da'wah  in  the  holy month  of  Ramadan  in  the  Darussalam  Mosque  Kampung  Pisang  Sorong  City  west  Papua.  The  da'wah activity in question is a routine lecture by the dai (preachers) conducted every night of ramadan that has been  programmed  by  the  Ministry  of  Religious  Affairs  of  Sorong  City.  This  research  uses  qualitative research type. As for data collection, researchers use interview methods to primary informants, namely the management  of  The  Darussalam  Mosque  Kampung  Pisang,  the  dai  /  mubaligh  listed  in  the  schedule  of lectures, worshipers (mad'u) Darussalam Mosque Kampung Pisang, and the Ministry of Religious Affairs that compiled the schedule of the lecture.As for the observation method, the author directly observes the situation in the field both from BKM / the manager of The Darussalam Mosque Kampung Pisang, Jamaah (mad'u) Masjid Darussalam Kampung Pisang, the dais listed in the lecture schedule, and the Ministry of Religion.This research is expected to be a reference in overcoming the vacancy according to the causative factors  in  the  holy  month  of  Ramadan  throughout  the  Mosque,  especially  in  the  Darussalam  Mosque Kampung Pisang. Thus da'wah activities can run well without any obstacles.Keywords: Dai and his personality, the cause of the vacancy dai, the efforts of the Ministry of ReligionAbstrakTujuan  penelitian  untuk  mengkaji  faktor-faktor  penyebab  terhambatnya  kegiatan dakwahdi  bulan  suci Ramadhan  di  Masjid  Darussalam  Kampung  Pisang  Kota  Sorong  Papua  Barat.  Kegiatan  dakwah  yang dimaksud  adalah  pengajian  rutin  oleh  para  dai  yang  dilakukan  setiap  malam Ramadhan yang  telah diprogramkan  oleh  Kementerian  Agama  Kota  Sorong.  Penelitian  ini  menggunakan  jenis  penelitian kualitatif. Adapun untuk pengumpulan data, peneliti menggunakan metode wawancara kepada informan utama  yaitu  pengurus  Masjid  Darussalam  Kampung  Pisang,  para  dai/mubaligh  yang  tercantum  dalam jadwal  perkuliahan,  jamaah  (mad'u)  Masjid  Darussalam  Kampung  Pisang,  dan  Kementerian  Agama. Urusan  yang  menyusun  jadwal  kuliah.  Adapun  metode  observasi,  penulis  mengamati  secara  langsung keadaan  di  lapangan  baik  dari  BKM/pengelola  Masjid  Darussalam  Kampung  Pisang,  Jamaah  (mad'u) Masjid   Darussalam   Kampung   Pisang,   mimbar   yang   tercantum   dalam   jadwal   perkuliahan,   dan Kementerian  Agama.  Penelitian  ini  diharapkan  dapat  menjadi  acuan  dalam  mengatasi  kekosongan menurut faktor penyebabnya pada bulan suci Ramadhan di seluruh Masjid khususnya Masjid Darussalam Kampung Pisang. Dengan demikian kegiatan dakwah dapat berjalan dengan baik tanpa ada hambatan.Kata kunci: Dai dan kepribadiannya, penyebab kekosongan dai, Kementerian Agama